2006
DOI: 10.1007/s11262-005-6912-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Differentiation and Phylogenetic Analysis of Cucumber Mosaic Virus Isolates from Cucurbits in the Northwest Region of Iran

Abstract: One hundred and twenty three cucurbit samples with one or more symptoms of leaf mosaic, leaf distortion, fruit mosaic, stunting, mottling and yellowing were collected from several locations in the northwest region of Iran. Screening by double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) with a cucumber mosaic virus (CMV) polyclonal antibody, produced positive reactions from 13 samples. However, none of these positive samples reacted with a CMV subgroup-II (S-II)-specific monoclonal antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Mgh91 and Jol186 isolates were placed in subgroup IA by Nematollahi et al (2012) in their study to assess CP and MP genes, and draw a phylogenetic tree. LORA, LORB, LORD, LORE and LORH were placed in subgroup IA close to S337 and E5 isolates (Bashir et al 2006). Khn1 and Esf172 isolates from East Azerbaijan province of Iran, by assessing CP and MP genes, were placed in subgroup IB and LARC, LORF and LORG isolates in our research were grouped with Khn1 and Esf172 isolates (Nematollahi et al 2012).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Mgh91 and Jol186 isolates were placed in subgroup IA by Nematollahi et al (2012) in their study to assess CP and MP genes, and draw a phylogenetic tree. LORA, LORB, LORD, LORE and LORH were placed in subgroup IA close to S337 and E5 isolates (Bashir et al 2006). Khn1 and Esf172 isolates from East Azerbaijan province of Iran, by assessing CP and MP genes, were placed in subgroup IB and LARC, LORF and LORG isolates in our research were grouped with Khn1 and Esf172 isolates (Nematollahi et al 2012).…”
Section: Discussionsupporting
confidence: 52%
“…It has been shown that 80% of the known isolates belong to subgroup I and the frequency of subgroup IA is more than that of IB (Gallitelli 2000). Group II is more common in cold climates (Roossinck 2002) and since Iran is a subtropical country, it was expected that more Iranian isolates would belong to group I, although group II has been reported from Iran (Bashir et al 2006;Sokhandan et al 2007;Rasoulpour and Izadpanah 2008;Nematollahi et al 2012). In our research, we detected IB subgroup strains from melon in Iran for the fi rst time.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Banana, cucurbit, tomato, and pepper are the crops most commonly affected by CMV (Palukaitis and GarciaArenal, 2003;Bashir et al, 2006;Dubey et al, 2010). A total of 300 samples were collected from three banana growing states in different geographical areas in India.…”
Section: Discussionmentioning
confidence: 99%
“…The CMVCP gene was previously amplified from an Iranian CMV isolate (B13) by PCR, cloned in pTZ57R/T and sequenced with the following accession number AY871070 (13). Here, the CMV CP gene was subcloned from pTZ57C The diagram was generated by the use of the plasmid processor (15).…”
Section: Cloning and Sequencingmentioning
confidence: 99%